The Impact of COVID-19 Crisis on Subnational Public Finance : The Case of Danang City - World Bank (World Bank, Washington, DC, 2021)
The national economy of Vietnam was affected by the April 2020 lockdown meant to contain the domestic spread of the COVID-19 (coronavirus) virus and subsequent outbreaks in Da Nang and Ho Chi Minh City. Nevertheless, the economy showed exceptional resilience. Gross domestic product (GDP) grew by an estimated 2.9 percent in 2020, one of the few economies in the world that grew during the pandemic. At the sectoral level, the services sector, especially the tourism-related subsectors, have borne the brunt of the COVID-19 crisis, with accommodation and catering services dropping by about 15.0 percent in 2020 compared to 2019, while the number of foreign visitors in 2020 was only 21 percent of the number a year ago.